2016
DOI: 10.1891/1946-6560.7.1.26
|View full text |Cite
|
Sign up to set email alerts
|

Coercive Control, Posttraumatic Stress Disorder, and Depression Among Homeless Women

Abstract: Intimate relationships involving psychological abuse, particularly those characterized by coercive control (CC), a pattern of behaviors aimed at gaining control over one's romantic partner, have been associated with poorer mental health for victims than among victims of physical partner abuse alone (Johnson & Leone, 2005). This study investigated whether CC predicted posttraumatic stress disorder (PTSD) and depression above and beyond the effects of childhood maltreatment and frequency and severity of physical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 47 publications
1
7
0
Order By: Relevance
“…The study findings resonate with research reporting that being homeless is hard for women (Bonugli et al, 2013;Edens et al, 2011;Finfgeld-Connett, 2010;Levine et al, 2016;Lovejoy, 2015;Welch-Lazoritz et al, 2015). It is unsafe and is a traumatic experience in and of itself (Bassuk & Beardslee, 2014;Whitbeck et al, 2015).…”
Section: It Was Pretty Brutal But It Was Definitely Worth Doing-violetsupporting
confidence: 75%
See 4 more Smart Citations
“…The study findings resonate with research reporting that being homeless is hard for women (Bonugli et al, 2013;Edens et al, 2011;Finfgeld-Connett, 2010;Levine et al, 2016;Lovejoy, 2015;Welch-Lazoritz et al, 2015). It is unsafe and is a traumatic experience in and of itself (Bassuk & Beardslee, 2014;Whitbeck et al, 2015).…”
Section: It Was Pretty Brutal But It Was Definitely Worth Doing-violetsupporting
confidence: 75%
“…Research reports that for women, trauma histories often create conditions that remove the option for remaining at home and are often the main catalyst for the women becoming homeless (Levine & Fritz, 2016;Metraux & Culhane, 2016). However, unlike much of the existing research that positions women as victims of violence, abuse and physical and mental ill-health (Broll & Huey, 2020;Hudson et al, 2010;Larney et al, 2009), this study indicated that even when facing homelessness women exit these situations with a sense of hope for a better future.…”
Section: It Was Pretty Brutal But It Was Definitely Worth Doing-violetmentioning
confidence: 58%
See 3 more Smart Citations